Adsorption and desorption kinetics of anionic dyes on doped polyaniline - Mahanta, Debajyoti; Madras, Giridhar; Radhakrishnan, S.; Patil, Satish (Journal of Physical Chemistry B, 2009)
In this study, we report an approach for the adsorption and desorption of anionic (sulfonated) dyes from aqueous solution by doped polyaniline. In this study, we have synthesized PANI with two dopants, namely, p-toluenesulfonic acid (PTSA) and camphorsulfonic acid (CSA), and used these to adsorb various dyes. It was found that the doped PANI selectively adsorbs anionic dyes and does not adsorb cationic dyes. The adsorption of anionic dyes causes the variation in electrical conductivity of PANI, indicating its potential as a conductometric sensor for these dyes at very low concentration. The adsorbed dyes were desorbed from the polymer by using a basic aqueous solution. The adsorption and desorption kinetics of the dye in the presence of doped PANI were also determined.